Effects of early or late clamping of the umbilical cord on hemoglobin in infants born vaginally at 2700 meters above sea level - Tapia Correa, Roxana Magaly (2015)
Several studies have shown that late cord clamping increases levels of hemoglobin in newborns. Objectives: To determine whether delayed umbilical cord clamping in term infants show higher hemoglobin levels than early clamping, investigation performed at 2700 m.a.s.l. Design: Prospective, randomized, double blind study. Setting: Gynecology and Obstetrics Department, Hospital Regional de Cajamarca, Peru. Participants: Newborns and their mothers. Methods: In January 2014, 100 pregnant women in labor with singleton pregnancies at term and without other risk factors were randomized to delayed clamping (when the umbilical cord stopped beats in 1-3 minutes) or early clamping (about 10 seconds after birth). Time was measured starting when baby shoulders appeared. A blood sample from the right newborn’s heel was obtained and placed in 2 capillaries, at birth and also at 6 hours of life; hemoglobin, hematocrit, and group and Rh factor were analyzed. Main outcome measures: Hemoglobin levels. Results: Ninety-one per cent of pregnant women did not have anemia and 9% had anemia; maternal blood group was O+ in 86%; 94% of newborns weighed 2 501-3 999 g, Apgar >7 was found in all newborns. Late clamping was done in 52 infants and early clamping in 48. The umbilical cord stopped beating at 2.67+-0.28 minutes. In 100% of infants with early clamping hemoglobin value was <15 mg/dL, and in late clamping 71.1% had hemoglobin 15.1 - 20.1 mg/dL and 28.9% over 20.1 mg/dL. There was no significant difference in newborn hemoglobin values whether the mother presented anemia or not. Conclusions: Late clamping resulted in better neonatal hemoglobin values. Average time for the umbilical cord stopping beats was 2.67 min. Maternal anemia did not affect neonatal hemoglobin at 2 700 m.a.s.l.